Misconceptions and Their Remediation on High School Physics Temperature and Heat Materials: A Systematic Review - YUDI, MUHAMMAD WAHYUDI; Mufit, Fatni; Festiyed, Festiyed; Hidayati, Hidayati (Journal of Innovative Physics Teaching, 2024)
This study aims to explore misconceptions in temperature and heat concepts in high school physics and analyze the effectiveness of remediation strategies. The objectives of the study are: (1) to identify the concepts most affected by misconceptions, (2) to analyze diagnostic tests frequently used to detect misconceptions, (3) to evaluate the methods/models/strategies used to remediate these misconceptions, and (4) to assess the impact of these strategies on students’ conceptual understanding. A systematic review of existing research articles was conducted using both qualitative and quantitative approaches. The results revealed that phase change concepts had the highest percentage of misconceptions (83%), while heat concepts had the lowest (12.42%). The Certainty of Response Index (CRI) was the most commonly used diagnostic tool (57.15%). Effective remediation strategies identified included Conceptual Understanding Procedures, Predict Observe Explain (POE), Problem-Based Learning (PBL), and Problem Solving. The study found that the average effect size of remediation strategies was 2.07, indicating a significant improvement in students’ understanding. The findings suggest that targeted diagnostic tests and remediation strategies can effectively reduce misconceptions and improve students’ understanding of temperature and heat concepts.